2005
DOI: 10.1021/ja055744x
|View full text |Cite
|
Sign up to set email alerts
|

Regiospecific and Stereoselective Syntheses of (±)-Reserpine and (−)-Reserpine

Abstract: Full details of three approaches to an entirely regio- and stereoselective synthesis of the well-known target reserpine are described, culminating in a total synthesis which efficiently meets these requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 54 publications
0
33
0
Order By: Relevance
“…Of note, the latter observation is in line with the observed diastereoselectivity for the thermal cyclization of aminonitrile 3 in refluxing acetonitrile reported by Stork. 12,13 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, the latter observation is in line with the observed diastereoselectivity for the thermal cyclization of aminonitrile 3 in refluxing acetonitrile reported by Stork. 12,13 …”
Section: Resultsmentioning
confidence: 99%
“…1,2,3,4,5,6,7,8 While there have been many elegant syntheses to arrive at specific members of this class, 9,10,11,12,13,14,15,16,17,18,19,20 especially the archetypal member, reserpine ( 2 , Figure 1), a unified approach to these molecules remains an unsolved problem. 21 In the realm of complex molecule assembly, the total synthesis of 2 by R. B. Woodward and co-workers is well recognized as a milestone event.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…76 Stork later also relied upon a similar analysis in his synthesis of reserpine. 77 Unfortunately, some of the reserpine thus produced underwent oxidation under the reaction conditions to generate the iminium ion 164 . Although reduction of 164 with hydride ion provides isoreserpine with high stereoselectivity, the zinc metal promoted reduction of 164 had been reported to give reserpine with high selectivity under certain conditions.…”
Section: Applications Of Diels–alder Reactions To Alkaloid Synthesismentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18] The pioneering chemical synthesis of α-amino acids reported by Adolph Strecker in 1850 made use of their close relationship with α-aminonitriles and even today, the Strecker synthesis is still used for the industrial scale synthesis of α-amino acids like methionine. 19 Due to the strong anion stabilizing capacity of the nitrile group and the latent iminium ion reactivity, [20][21][22][23] α-aminonitriles are not only useful precursors to amino acids but also versatile building blocks for the synthesis of a wide variety of nitrogen-containing compounds 24, 25 including diverse N-heteroarenes, [26][27][28] aliphatic amine derivatives 29,30 or alkaloids [31][32][33][34][35][36][37][38][39] . We found that N-mono-and N-unsubstituted α-aminonitriles derived from aromatic or heteroaromatic aldehydes can be deprotonated quantitatively in α-position to furnish stabilized α-aminocarbanion equivalents and in contrast to their counterparts derived from aliphatic aldehydes, no N-protection is required.…”
Section: Page 1 Of 24 Acs Paragon Plus Environmentmentioning
confidence: 99%